The Transcription of the -ic, -ical, and ics Suffixes in the Indonesia Language - Zaenal Arifin Toy (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2003)
When the Dutch language was used nation- wide in this country several decades ago, the Indonesian language had much been influenced by it. A lot of Dutch words were absorbed unto the Indonesian language. One of the influences which still exists up to the present time is about the transcription of the Dutch words having the isch sufixes transcribed into is in the Indone- sian language. Some other words have been transcribed in the same way such as: logisch into logis, egoistich egonstis, democratisch into demokratis, praktisch into praktis, historisch into historis, medisch into medis, etc.